Revealing the sensory impact of different levels and combinations of esters and volatile thiols in Chardonnay wines. Issue 1 (January 2023) - Iobbi, Angelica; Di, Yanming; Tomasino, Elizabeth
Abstract: The assessment of different aroma families on tropical fruit aroma perception is still not well understood. This study aimed to investigate the effect of esters and volatile thiols on tropical fruit aroma perception in white wines. Four levels of thiols (none, low, medium and high) and three levels of esters (none, low, medium) were added to a dearomatized white wine base in a full factorial design. Check-All-That-Apply (CATA) was used to determine the aroma descriptors that most differentiated the wines followed by Sensory Descriptive Analysis (SDA) to evaluate the intensity of those significant aroma attributes. More than 78% of the total variance was described in the first two dimensions when using Canonical Variate Analysis. Tropical fruit aromas were associated with wines containing different levels of esters and ester-thiol combinations. Volatile thiols alone imparted an earthy aroma and were grouped with the control wine. The different ester-thiol combinations altered the tropical fruit aroma quality in the wines from citrus to passionfruit, pineapple and guava. Understanding the cause of tropical fruit aroma allows for targeted processing to achieve the desired wine sensory quality.